Oculopharyngeal myopathy with inflammation and calcinosis: an unusual phenotype. Issue 6 (12th February 2008) - Jenkins, T; Al-Sarraj, S; Rose, M
Abstract : The case is reported of a patient with progressive proximal and distal weakness, dysphagia, respiratory weakness, calcifications, ptosis and ophthalmoparesis with inflammation, rimmed vacuoles and positive amyloid and ubiquitin on muscle biopsy. The histopathological features fit best with inclusion body myositis, but ophthalmoparesis and ptosis have not previously been described. The clinical phenotype fits best with hereditary inclusion body myopathy or distal-oculopharyngeal muscular dystrophy, but the degree of inflammation seen is unusual. None of these are associated with calcinosis.